ANALISIS STRATEGI BIMBINGAN BELAJAR UNTUK MENGATASI KESULITAN BELAJAR SISWA - Siti Nur Azizah; Syfa Maulidiyah; Rahmi Anekasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze tutoring strategies for addressing elementary school students' learning difficulties and the role of teachers in helping students achieve optimal learning outcomes. The research method used was a literature review, collecting data from various sources, such as books, journals, and relevant scientific articles. The data were analyzed descriptively and qualitatively through a process of grouping, interpreting, and drawing conclusions from the information obtained. The results indicate that students' learning difficulties are influenced by internal and external factors. Internal factors include low learning motivation, a lack of basic reading, writing, and arithmetic skills, and low self-confidence. Meanwhile, external factors include an unsupportive learning environment, monotonous teaching methods, and a lack of support from family and the surrounding community. To address these issues, teachers implement various strategies, such as remedial learning, individual approaches, the use of innovative learning methods and media, providing motivation and positive reinforcement, and collaborating with parents. Furthermore, guidance and counseling teachers play a crucial role in helping students identify learning problems and find appropriate solutions through guidance and mentoring services. Based on the study results, it can be concluded that appropriate, flexible, and student-centered tutoring strategies can help reduce learning difficulties and improve student motivation and learning outcomes. Therefore, effective collaboration between teachers, parents, and the school environment is necessary for the learning process to run effectively and optimally.